Sabar dalam Perspektif Islam dan Barat - M Yusuf (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2018)
advances in science and technology are like two sides of the coin, it could be a disaster, while humans are not ready and hasn't been able to go with the flow of such changes. Inability to adjust to these changes can give rise to tension or stress on him. The teachings of Islam with universal, covering all the dimensions of human life, including problems of human material or mental (psychic). Patient in facing changes the massif became a strategic point to develop human capacity to explore change the world. Education patience recorded in Q. S al-Baqarah verse 45, 153, 294 and ali-Imran, verse 125, 186, 200. On the other hand the patience had the function as a solution of the problem, people who implement the problematic nature of the patient will feel easy through obedience to God and his Messenger. Wait as the system of psychological defense mechanism to cope with the dynamic test faced by man as God's Caliphs on Earth. Patient in the Western perspective is known for its patient and patience, and have some other equivalent variants, among them; 1) self-control; 2) Resiliensi; Perseverence. 3); 4) Acceptence